Novel SPEG variant cause centronuclear myopathy in China. Issue 2 (18th October 2019) - Tang, Jia; Ma, Wei; Chen, Yangran; Jiang, Runze; Zeng, Qinlong; Tan, Jieliang; Jiang, Hongqing; Li, Qing; Zhang, Victor W.; Wang, Jing; Tang, Hui; Luo, Liangping
Abstract: Background: Centronuclear myopathy (CNM), a subtype of congenital myopathy (CM), is a group of clinical and genetically heterogeneous muscle disorders. Centronuclear myopathy is a kind of disease difficult to diagnose due to its genetic diversity. Since the discovery of the SPEG gene and disease‐causing variants, only a few additional patients have been reported. Methods: A radiograph test, ultrasonic test, and biochemical tests were applied to clinical diagnosis of CNM. We performed trio medical exome sequencing of the family and conservation analysis to identify variants. Results: We report a pair of severe CNM twins with the same novel homozygous SPEG variant c. 8710A>G (p.Thr2904Ala) identified by clinical trio medical exome sequencing of the family and conservation analysis. The twins showed clinical symptoms of facial weakness, hypotonia, arthrogryposis, strephenopodia, patent ductus arteriosus, and pulmonary arterial hypertension. Conclusions: Our report expands the clinical and molecular repertoire of CNM and enriches the variant spectrum of the SPEG gene in the Chinese population and helps us further understand the pathogenesis of CNM.